Analisis Pendapatan Non Halal Perbankan Syariah Di Indonesia: Sumber Dan Penggunaannya - Hartanto, Rudy; Pramono, Irena Paramita; Purnamasari, Pupung (Falah: Jurnal Ekonomi Syariah, 2019)
The existence of the regulation for Islamic banking causes it to conduct its activities by the guidance of Islamic principles which avoid some non-halal sources of income. On the other hand, the transactions between Islamic banking and conventional banking are unavoidable because conventional financial institutions still dominate all transactions in each country. This means that non-halal sources of income cannot be avoided, by the way of the transaction is done. This research aims to analyze on the sources of income and its distribution of the non-halal funds of Islamic Banks in Indonesia. This research is quantitative. The method of collecting data documentation uses data from 2015-2017 with a total sample of 102 Islamic banks. The results show that there were differences in the average non-halal funds of Islamic Commercial Banks with Islamic Business Unit Bank. In addition, this study shows that Islamic commercial bank tends to have non-halal funds bigger than Islamic Business Unit Bank. On the other hand, the result shows that non-halal funds sources in the banking industry are dominated by interest income from another conventional bank and the using of non-halal funds is dominated by social activities.